CORPUS-ASSISTED DISCOURSE STUDY (CADS): WOMEN WITH DISABILITIES IN KOMPAS.COM’S NEWS REPORTING - Yenny Karlina (Universitas Negeri Makassar, 2023)
The interaction of gender and disability has gained attention in academia and activism, emphasizing the importance of combating prejudice and stigma encountered by women with disabilities. The portrayal of this group in the media is critical because it has the potential to either perpetuate stereotypes or contribute to constructive societal change. The study,